A qualitative study of sexual behaviours among methamphetamine users in Chiang Mai, Thailand: A typology of risk - Susan G. Sherman (2018)
Introduction and Aims. Methamphetamine (MA) has become the leading drug of abuse in northern Thailand over the past several years, particularly among youth. The current qualitative study explores the relationship between sexual behaviours and MA. Design and Methods. Between March 2002 and January 2003, 48 in-depth interviews with young MA users aged 15-2 years in Chiang Mai. Interviews were transcribed verbatim in Thai and translated into English. Data were analysed inductively using the constant comparative method common to grounded theory methods. Atlas-ti was used for data management. The current analysis was stratified by gender. Results. Participants were 44% male and the median age was 20 years. At the time of the interviews, 70% were not using MA. A typology of experiences with and feelings about MA's relationship to sexual activity emerged: (1) enhanced libido - individuals who found that MA enhances their sexual experiences (n=13); (2) decreased libido or no effect - individuals who found that MA detracted from sexual desire (n=22); and (3) virgins (n=13). Discussion and Conclusions. Participants reported several distinct patterns of relationship between MA and sex. Tailored interventions are needed that address specific patterns of sexual behaviors among youth in order to promote sustainable safer sex behaviours in this population. [Sherman SG, Gann D, German D, Sirirojn B, Thompson N, Aramrattana A, Celentano DD. A qualitative study of sexual behaviours among methamphetamine users in Chiang Mai, Thailand: a typology of risk. Drug Alcohol Rev 2008;27:263-269].